Analisa pengaruh kualitas udara dan kelayakan investasi proyek penggantian AC pada gedung kantor PT ISM, Tbk - Div Bogasari Surabaya dengan pendekatan aspek finansial - Rosyid, Abdoel; Nurrajendra, Angghisna Richard (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The financial aspect is an important factor in any investment project. The purpose of this analysis is to be able to find out the effect on air quality and assess the feasibility of a project investment in replacing a conventional ductless ceiling AC with a Daikin VRV inverter AC. This research was conducted using a quantitative descriptive method. Based on the results of the analysis of this study, this project can provide significant energy savings and can reduce CO2 carbon emissions, which can have a better impact on air quality in the surrounding environment. There are several parameters used to review the feasibility of investing in this project, namely net present value (NPV), internal rate of return (IRR), benefit cost ratio (BCR), and payback period (PP). Some of these parameters can be used to determine the project's feasibility, with the analysis yielding an NPV of IDR 791,244,535, an IRR of 5.95%, a BCR of 1,185, and a PP of 4.2 years. Based on the NPV, IRR, BCR, and PP to ensure the project's financial viability and the effect on air quality, replacing this air conditioner can reduce CO2 emissions by 23.5 tons of equivalent CO2 per year.